Moisture effects on mechanical behavior of CNF-RGO nanocomposites showing electrical conductivity. (December 2022) - Mianehrow, Hanieh; Li, Lengwan; Olsén, Peter; Berglund, Lars
Abstract: Water-processed nanocomposites based on cellulose nanofibrils (CNF and 2D platelets are sustainable alternatives to nanocomposites from fossil-based polymers. The degree of dispersion of 2D platelets in CNF matrix is critical to mechanical properties, but reduced graphene oxide (RGO) has poor hydrocolloidal stability. This is addressed by forming electrically conductive and strong CNF-RGO nanocomposites by green chemical reduction of wet, vacuum-filtered CNF-GO cakes, taking advantage of the colloidal dispersibility of GO platelets in CNF, as characterized in the solid nanocomposite by SAXS, WAXS and FE-SEM. CNF-RGO nanocomposite with 2 wt% RGO shows a Younǵs modulus of 20.4 GPa and tensile strength of 319 MPa, with considerable ductility at 50 % RH. Although CNF-GO shows much higher moisture sorption than CNF-RGO at 90 %RH, the CNF-GO mechanical properties are higher, for thermodynamic reasons, MD simulations predict dry, hydrogen-bonded CNF-GO interfaces even in wet conditions, and this can explain the better performance of CNF-GO.